COVID Angels Fighting Daily Demons? Mental Health of Healthcare Workers and Religion - Emilia Barili; Paola Bertoli; Veronica Grembi; Veronica Rattini (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2021)
Relying on a unique survey of more than 15,000 respondents conducted from June to August 2020 in Italy, we show that priming religiosity in healthcare workers decreases the level of self-assessed mental distress experienced during the first wave of the COVID-19. We show that priming religiosity decreases self-assessed mental distress by 9.5%. Consistent with the idea that religiosity serves as a coping mechanism, this effect is stronger for the more impacted categories (e.g., hospital workers) and for respondents facing more stressful situations, such as being reassigned due to the COVID-19 emergency or working in a COVID-19-related specialty (e.g., emergency care), among others. Moreover, higher effects occurs also among physicians who self-classify as religious, while this distinction does not apply for nurses.
Keywords: I10; N34; Z12; 330; Healthcare Workers; COVID-19; Mental Health; Coping Mechanisms; Religiosity